2019
DOI: 10.1080/02619768.2019.1652899
|View full text |Cite
|
Sign up to set email alerts
|

The research circle - a tool for preschool teachers’ professional learning and preschool development

Abstract: The article explores a professional learning programme, a research circle, in which preschool teachers and researchers collaborate on content relating to sustainable development, science and technology. It investigates how collaborations between preschool teachers and researchers can contribute to professional learning and preschool development. The research focuses on experiences of participation in research circles and makes use of Participatory Action Research (PAR). The data consists of twelve preschool te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…Both practitioner research and inquiry are a form of professional development aimed at understanding and improving practices within the teacher's local context from an insider perspective (Borko, Liston, and Whitcomb 2007;). It offers a range of potential outcomes, such as improving teaching practice (e.g., Ermeling 2010;Pareja Roblin et al 2014), increasing teachers' knowledge and understanding of students (e.g., Butler and Schnellert 2012;Elm and Nordqvist 2019;Jacobs, Yendol-Hoppey, and Dana 2015;Willegems et al 2018), and fostering teacher empowerment and transformation (e.g., Dana and Yendol-Hoppey 2019;Esposito and Smith 2006). Learning how to conduct practitioner inquiry in teacher education can lead to an increased critical, reflective and innovative attitude and a better understanding of scholastic culture; it can also prompt participation in professional learning communities (Cochran-Smith and Lytle 2009;Dobber et al 2012;Willegems et al 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Both practitioner research and inquiry are a form of professional development aimed at understanding and improving practices within the teacher's local context from an insider perspective (Borko, Liston, and Whitcomb 2007;). It offers a range of potential outcomes, such as improving teaching practice (e.g., Ermeling 2010;Pareja Roblin et al 2014), increasing teachers' knowledge and understanding of students (e.g., Butler and Schnellert 2012;Elm and Nordqvist 2019;Jacobs, Yendol-Hoppey, and Dana 2015;Willegems et al 2018), and fostering teacher empowerment and transformation (e.g., Dana and Yendol-Hoppey 2019;Esposito and Smith 2006). Learning how to conduct practitioner inquiry in teacher education can lead to an increased critical, reflective and innovative attitude and a better understanding of scholastic culture; it can also prompt participation in professional learning communities (Cochran-Smith and Lytle 2009;Dobber et al 2012;Willegems et al 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Es necesario establecer colaboraciones continuadas y fluidas entre Universidad-escuela que permitan contribuir a la mejora del aprendizaje profesional de los docentes y, consecuentemente, al desarrollo preescolar (Elm y Nordqvist, 2019). Además, desde el campo de la Didáctica de las Ciencias Experimentales esta colaboración es fundamental para detectar necesidades y expectativas de las escuelas y para que los hallazgos de la investigación lleguen a las aulas.…”
Section: Conclusiones E Implicaciones Educativasunclassified
“…Through practice-developing school research, teachers' professional knowledge base can be strengthened and developed [6]. Continuing professional learning among teachers is necessary for supporting and encouraging the improvement of knowledge and practice (e.g., [7]). One way to keep this is by conducting different forms of professional development programs for teachers in school (e.g., [7]).…”
Section: Introductionmentioning
confidence: 99%
“…Continuing professional learning among teachers is necessary for supporting and encouraging the improvement of knowledge and practice (e.g., [7]). One way to keep this is by conducting different forms of professional development programs for teachers in school (e.g., [7]). Previous research has shown that professional development positively influences teachers' capacity to reflect on new knowledge and practices [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation